Biomimetic production, characterisation, in vitro cytotoxic and anticancer assessment of aqueous extract-mediated AgNPs of Teucrium stocksianum Boiss - Ullah, Ikram; Abamor, Emrah Sefik; Bagirova, Melahat; Shinwari, Zabta Khan; Allahverdiyev, Adil M. (WILEY, 2018)
Owing to the numerous biological applications, cost effectiveness and low cytotoxicity of the biomimetic nanoparticles (NPs), the authors optimised the production of silver NPs (AgNPs) using aqueous extract of Teucrium stocksianum Boiss. The NPs were characterised by ultraviolet-visible (UV-vis) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), dynamic light scattering (DLS) and Fourier transform-infrared spectroscopy (FTIR). The UV-vis spectroscopy revealed a surface plasmon resonance (410-440nm) at an incubation temperature of 90 degrees C when 1mM Ag nitrate combined to 5mg/ml extract concentration in the ratio of 1:10. DLS results show an average zeta size of approximate to 44.61 nm and zeta potential of -15.3mV. SEM and XRD confirmed the high crystallinity and cubical symmetry with an average size below 100nm. FTIR measurement shows the presence of various functional groups, responsible for the capping and reduction of Ag metal. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell viability assay shows that AgNPs are less cytotoxic to J774 and L929 cells as compared with enhanced anticancer activity with low IC50 concentrations (68.24 mu g/ml) against Michigan Cancer Foundation-7 (MCF-7) cells. The ethidium bromide/acridine orange assay shows that the AgNPs kill the cell by apoptosis. Overall, the results show that AgNPs possesses potent anticancer activities.
Keywords: cellular biophysics; cancer; nanobiotechnology; nanomedicine; ultraviolet spectra; X-ray diffraction; scanning electron microscopes; light scattering; patient treatment; anticancer assessment; in vitro cytotoxic assessment; aqueous extract-mediated AgNPs; Teucrium stocksianum Boiss; nanoparticles; biological applications; biosynthesis; silver NPs; scanning electron microscopy; dynamic light scattering; Fourier transform-infrared spectroscopy; UV-vis spectroscopy; surface plasmon resonance; extract concentration; zeta potential; high crystallinity; FTIR measurement; amide molecules; viability assay; enhanced anticancer activity; potent anticancer activities; SYNTHESIZED SILVER NANOPARTICLES; GREEN SYNTHESIS; LEAF EXTRACT; INDUCED HEPATOTOXICITY; APOPTOSIS; TOXICITY; ANTIBACTERIAL; CELLS; GOLD; Biochemistry & Molecular Biology; Science & Technology - Other Topics